COMPARATIVE EFFECTIVENESS AND ADVERSE EFFECTS OF INTERFERON ALPHA-2b PLUS RIBAVIRIN THERAPY IN HEPATITIS '˜C' FOR 26 WEEKS - Ali, Shafqut; Iram, Samia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Hepatitis C is major emerging challenge for pathologists and treating physicians all over the world. Already 10 million Pakistani population has become anti-HCV positive. It is not only affecting hepatobiliary system but with passage of time research is revealing that Hepatitis C is going to involve almost every organ of the body. With timely diagnosis and treatment, millions of patients can be saved from morbidity and mortality. The nation has to sacrifice initial economic allocations to avoid later millions of mortalities and greater economic losses on affected patients and to support their families. The objective of this study was to evaluate effectiveness of combine therapy of Hepatitis C in local population of Pakistan. Methods: This case series study was done at CMH Okara, Kohat, Abbottabad, and PAF Hospital, Shorkot from August 2000 to August 2009. All 1,000 patients from 10 to 60 years of age, confirmed anti-HCV Positive by ELISA and PCR Positive for HCV RNA, were subjected to Interferon alpha-2b and Ribavirin therapy for similar period of time. Response and adverse affects were observed by clinical examination, blood complete picture including platelet count and ALT fortnightly. PCR for HCV RNA and ultrasound abdomen (hepatobilliary system) was done quarterly during treatment and 6 monthly for 2 years after treatment to review the sustained response and relapse. Results: Over all cure rate after 2 years was 855 (85.5%) excluding the 50 (5%) of initial resistant to one year treatment and 95 (9.5%) re-treated relapse cases. One hundred and forty-five (14.5%) patients were found to be resistant to treatment. Conclusion: Hepatitis C must be treated timely after proper diagnosis. Interferon and Ribavirin combination have shown high '˜cure' rate in Hepatitis C. In spite of high cure rate of 85.5% with timely and proper treatment, low socio-economic status is a major problem for poor individuals to get treatment. Preventive aspect must be strictly followed and implemented. Keywords: HCV, Anti-HCV, PCR, ALT, ELISA, Interferon alpha-2b, Ribavirin, Adverse effects